The effects of using student oriented learning management System (E-Solms) on Student’s Motivation - Khairul Azhar Mat Daud; Mohd Ali Samsudin (http://www.bjournal.co.uk/paper/BJASS_10_2/BJASS_10_02_01.pdf, 2012)
Motivation is an important factor in learning and teaching environment to ensure students’ continuous learning. In the adults learning style, Self Directed Learning (SDL) is the most popular method to be implemented. Nowadays in ICT era, online learning will replace the conventional or face to face learning by a variety of reasons. In this paper, authors identify and determine the appropriate learning instruction to be designed and embedded in online self directed learning based on online SDL model are developed by Song and Hill, 2007. The research respondents are comprised 239 diploma students in mechanical engineering course at polytechnic under Ministry of higher Education, Malaysia. This study identifies the effect of online self directed learning on students’ motivation. Therefore, it can be concluded that online SDL can give positive impact on enhancement of students motivation. The finding of this research shows increase in the level of student motivation after implementation of online SDL (E-SOLMS).